Islamic Microfinance Model: Combination of Commercial and Social Models in MSMEs Fostered by BAZNAS Bojonegoro - Shofa Robbani; Mahesi Ernawati (DPPM Universitas Pelita Bangsa, 2025)
This research employs a qualitative descriptive approach to understand how the Islamic microfinance model, which combines social and commercial aspects, is implemented in micro, small, and medium enterprises (MSMEs) supported by Baznas Bojonegoro. The data in this study were collected through three main techniques, namely in-depth interviews with semi-structured guidelines to explore the experiences of business actors related to financing, repayment systems, assistance, and the economic and social impacts of the program; participatory observation by visiting the business location directly to observe operational activities and interactions between MSME actors and BAZNAS; and documentation in the form of collecting supporting documents such as financial reports, data on the development of fostered partner businesses, and economic program policies. The results indicate that the financing model implemented by the National Zakat Agency (BAZNAS) is an effective strategy in encouraging the economic mobility of mustahik so that they are able to transform into muzaki sustainably in the future.